Hubungan terapi manitol 20% dengan fungsi ginjal pada penderita stroke perdarahan intraserebral dengan peningkatan tekanan intrakranial - Anyta Prisca Dormida; Yuneldi Anwar; Puji Pinta O. Sinurat (Fakultas Kedokteran USU, 2014)
Background : Intracerebral hemorrhage can increase intracranial pressure. Treatment of increased ICP is one of the most important and most common problems. Mannitol has been seen as one of the first choices in the immediate-treatment of increased ICP. The most common complications of mannitol therapy are fluid and electrolyte imbalances, hypersensitivity reactions and might also cause renal failure even in therapeutic doses. However the influence of osmotherapy on renal function in patients treated with mannitol due to increased intracranial pressure was not so far well described.Method : This was a cross sectional study of 39 subjects in Haji Adam Malik General Hospital. Subjects were patients who diagnosed with stroke caused by intracerebral hemorrhage with increasing of intracranial pressure based on neurological examination and head CT scan examination and treated with mannitol 20% dose 0.5 g/kg body weight for 3 days. Renal function were measured before and after mannitol 20% administration.Results : Of 39 patients (21 males, 18 females), mannitol 20% administration showed changes of renal function parameter on the 3rd day. There were increasing of serum creatinine level 0.21 (SD 0.51) mg% (p=0.014), increasing of serum ureum level 18.44 (SD 25.7) mg% (p=0.000), increasing of serum osmolality 8.64 (SD 17.95) mmol/kgH2O (p=0.005) and decreasing of serum sodium level 3.03 (SD 6.68) mEq/L (p=0.007). Increasing of serum potassium level and decreasing of serum chloride level were also found (p>0.05). None of patients developed anuria or oliguria. There was decreasing of GFR 14.87 (SD 36.42) mL/menit (p=0.015), but none of patients developed acute renal failure. There was a significant relationship between creatinine level and serum osmolality on the 3rd day (r=0.415, p=0.009).Conclusion : Mannitol 20% administration for stroke caused by intracerebral hemorrhage with increasing of intracranial pressure showed changes of serum creatinine, ureum, osmolality and natrium level significantly (p<0.05) and also decreased of glomerular filtration rate (p<0.05).Keywords : mannitol 20%; renal function; stroke caused by intracerebral hemorrhage; intracranial pressure